Postpartum Care Services during the Fourth Stage of Labour in Bharatpur Hospital of Nepal - Chhetri, Dinesh; Paudel, Ashok Kumar; Baniya, Ambika; Gurung, Arfin; Karki, Khusbu (Journal of Karnali Academy of Health Sciences, 2021)
Background: Postnatal care is an important part of maternal care, as serious and life-threatening complications can occur in the postpartum period. So, this study was conducted to assess the quality of postpartum care services during the fourth stage of labour in the maternity ward of Bharatpur hospital in Chitwan district of Nepal.Methods: Cross-sectional hospital-based study was done among 218 women admitted in the maternity ward for vaginal delivery in Bhartapur hospital in Chitwan. A set of data collection tool was developed, pretested and finalized and face-to face interview was conducted. Part-1 of the tool was related to socio-demographic characteristics of respondents, Part-2 and 3 of the tools was used as a checklist to assess institutional characteristics and quality of postpartum care services respectively. The structured checklist had twenty-two items including twelve critical steps. The purpose of the study was explained to the respondents, verbal informed consent was obtained from respondents and ethical approval was obtained from the Institutional Review Committee of Chitwan Medical College.Results: The median age of the respondents was 23 years with minimum age 16 years and maximum 40 years. The significant association observed between postpartum care during the fourth stage of labour and residence of mothers (p=0.021).Conclusions: Based on the findings of this study, it can be recommended that Postpartum care in Bharatpur hospital needs to be improved and it would be better if plans and programs implemented with priority to enhance the capacity of staffs and health institutions to provide postpartum care services according to the WHO recommendation guideline.